Load displacement simulation of CP-Ti/UHMWPE hip implant - Handoko Handoko; Suyitno Suyitno; Rini Dharmastiti; Rahadyan Magetsari (Journal of Medical Physics and Biophysics, 2021)
Hip implant made from titanium is special due to its lower modulus of elasticity to avoid stress shielding with the human bone. One type of load the material designed to withstand is a gradually increased compressive force which happened when the patient change his/her position from sitting to standing. This study examined the capability of a metal on polymer (MOP) implant made from commercially pure titanium (CP-Ti) and ultra-high molecular weight polyethylene (UHMWPE) loaded up to 3 kN according to ISO 14242 standard. Two CP-Ti/UHMWPE MOP models with femoral diameter of 22 mm and 32 mm were simulated with finite element. The results expressed in load displacement curves were validated with compressive load experimental tests. Both materials are capable to withstand the load. Simulation data are in good agreement with the experiments.